Nasogastric Drip Rehydration Therapy in Acute Diarrhea with Severe Dehydration - Syamsul Hidayat; Srie Enggar K. D.; Nancy Pardede; Rusdi Ismail (Paediatrica Indonesiana, 1988)
WHO recommended severe dehydration without shock in acute diarrhea to be rehydrated by nasogastric drips (NGD) of oral rehydration solution (oralit). In this respect the criteria of a still palpable and countable pulse, the absence of meteorism and absence of complication, the reverse warranting iv fluid therapy, can be used as practical guidelines to identify the patient "without shock". A clinical trial comparing the result of NGD oralit rehydration therapy to that of intravenous Ringer-lactate on small children with diarrhea and severe dehydration was conducted. Seventy jive patients admitted to the Department of Child Health Palembang General Hospital from January up to July 1986, aged 1 to 59 months, suffering from acute diarrhea with severe dehydration fulfilled to above mentioned criteria. Randomly 36 were assigned to NGD rehydration therapy using WHO standard ORS (in Indonesia is named as oralit) and 39 were rehydrated with iv Ringer lactate solution, given in four hours consisting of 40ml/kg BW, 30ml/kg BW, 20 ml/kg BW and 20ml/kg BW in the first, second, third and fourth hours respectively. Based on the failure rate of rehydration in the first four hours, the recurrence of dehydration after rehydration and the side effects of fluid therapy, it was concluded that acute diarrhea cases with severe dehydration who fulfilled the above mentioned criteria can be rehydrated by NGD oralit as effective and safe as by iv Ringer lactate.